Estudio de prefactibilidad para la instalación de una planta productora de galletas saladas a partir de harina de linaza (linum usitatissimum) y orégano (origanum vulgare) - Andrade Hernandez, Cesar Elias (2023)
The purpose of this study is to evaluate the project’s technical, economic-financial, social and environmental viability. This project consists in the implementation of a crackers production plant based on linseed flour and oregano. The presentation of the product consists of a unit package of crackers of 50 grams. The dimensions of each unit package are 11 cm x 5.5 cm x 2cm. Likewise, these 6 unit packages will be found in a large package, the sale value considered will be S/ 3,00. In the market study, a project demand of 2 814 519 large packages of crackers was obtained by 2025. For this, people from Lima Metropolitan belonging to NSE A & B, who have a healthy lifestyle, practice some sport, or are interested in taking care of their health (60%) were considered as the target audience. Likewise, it was determined that the plant will be installed in the district of Lurin and will have a total area of 1026 m2. To calculate the size of the plant, the value obtained in the size-market relationship will be used. In relation to the equilibrium point, a value equal to 1 027 066 large packages. The maximum capacity of the plant is 2 914 626 large packages or 874 388 kg. Finally, the investment required for the implementation of the project will be S/ 3 274 916 and a financing of 40% will be made. Regarding the economic-financial evaluation of the project, it is known that the NPVE and NPVF are S/ 1 973 467 and S/ 2 304 080, respectively, these results indicate that the project is viable. Likewise, the IRRE and IRRF are equal to 37,68% and 50,34%, these values are greater than the COK (20%), this means that the project can be accepted. On the other hand, the Recovery Period (RP) obtained from the economic and financial evaluation are 2 and 11 months, respectively.